The adequacy of the judicial immunity of the diplomatic envoy in public international law - Altamimi, Abdulaziz Yousef Khamis Yousef (2023)
This study dealt with the issue of the efficiency of the judicial immunity of the diplomatic envoy in international law. This study aimed to study the legal framework for the judicial immunity of diplomatic missions under international law and evaluate the sources of diplomatic immunity for diplomatic missions and their efficiency. The importance of the study is to know the means of resolving disputes arising from the actions of a diplomatic envoy who enjoys judicial immunity, as they have special procedures and protocols, they are held accountable and punished according to the laws of their countries, considering the advantages of immunity. The problem of the study was represented in the contradiction between the powers of the judiciary and what is required by the requirements of the state's diplomatic job, and the state's sovereignty in imposing the jurisdiction of its courts on all individuals who committed crimes on its territory. In addition, the judicial immunity granted to the diplomatic envoy leads to a conflict between the harmony and compatibility between the envoy’s right to cling to diplomatic immunities and privileges, and the right of the state to protect its security from abusing the immunity presented to him, especially if the diplomat commits a crime on the territory of the country he is delegated to. The study adopted the analytical method in addition to the experimental process by conducting interviews with specialists in the field of study. The study reached several results, the most important of which is that diplomatic immunity is a fundamental pillar of international relations, by securing the best to carry out diplomatic functions and facilitating their sensitive tasks. In addition to securing its objectives based on managing the foreign affairs of international parties and strengthening their relations based on the principles and principles of equality and maintaining international peace and security. The study recommended the need to reconsider the 1961 Vienna Convention, especially with diplomatic relations, because this agreement came in response to the aspirations of the great powers after World War II.